The music and sound of experimental film - Rogers, Holly (Professor of music); Rogers, Holly (Professor of music); Barham, Jeremy, 1963-; Barham, Jeremy, 1963- (Oxford University Press, 2017)
This book explores the role of music and sound in experimental film from the earliest work of pioneers such as Walther Ruttmann to latter-day experiments with new and digital media. Chapters examine issues relating to the avant-garde, abstraction, animation, found footage, queer film, visual music and VJing.- Resumé vydavatel